Carbohydrate dependence during cycle-run successions in triathletes in the competitive season - Coste, O.; Galy, O.; Maimoun, L.; Raibaut, J. L.; Manetta, J. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The two most important sources of muscle energy during exercise are fat and carbohydrates (CHO), and substrate utilization depends in great part on exercise intensity and duration. When relative intensity (i.e., % of VO2max) increases, the energy derived from fat decreases in parallel to a corresponding rise in CHO dependence. During prolonged exercise, on the other hand, CHO utilization decreases while fat contribution increases (Holloszy and Kohrt, 1996). The balance of CHO and lipid metabolism during exercise is quite complex, however, and prior endurance training results in muscular biochemical adaptations that enhance lipid oxidation (Brooks and Mercier, 1994). Methods To investigate the effects of intensive training on CHO utilization during hard-intensity exercise, seven competitive triathletes performed four 50-min experimental cycle-run successions (30 min of cycling followed by 20 min of running) at a velocity requiring an O2 consumption of ~ 70 % of maximal over the course of a triathlon season, i.e., in February: ET1 (basic), May: ET2 (pre-competition), August: ET3 (competition, French championship), and November: ET4 (post-competition). Results CHO oxidation was determined by indirect calorimetry. % of CHO utilization during exercise was higher at ET3 in comparison with other periods (Fig. 1, P<0.05). Total CHO oxidation was higher at ET3 than at ET1 and was lower at ET4 than at ET3 (P< 0.05). However, CHO dependence was higher during cycling than running at ET3 (P<0.05). Training volume and intensity were decreased at ET4 (- 50 %, P<0.05) in comparison with other periods.' We conclude that competitive triathletes increase CHO oxidation during prolonged strenuous exercise after six months of intensive training, in association with the main athletic objective (the French championship), but show a decline by the end of the season concomitant to decreased training program. Thus, competitive triathletes present a higher CHO-dependence associated with a higher training volume and intensity during the course of the season.